Development of sustainable alkali-activated bricks using industrial wastes. (10th August 2019) - Gavali, Hindavi R.; Bras, Ana; Faria, Paulina; Ralegaonkar, Rahul V.
Graphical abstract: Highlights: Feasibility of industrial wastes in brick production is reviewed. Design and development of alkali-activated bricks are studied. Physico-mechanical and durability properties are reviewed extensively. The factors responsible for the brick performance are examined. Alkali activation provides sustainable solutions for brick production. Abstract: Brick is one of the majorly used building materials for masonry construction. Unlocking the potential to deliver significant impact against India's current housing and agro-industrial waste challenges is crucial. This can be met by developing sustainable products using industrial wastes. Alkali-activated products are claimed to be sustainable and cost effective, giving rise to Portland cement free products. The paper presents a state-of-the-art review on the development of sustainable bricks by alkali-activation of industrial wastes. Physical and chemical characterisation of industrial wastes are discussed in order to check its feasibility for the development of alkali-activated bricks. The influence of parameters on physico-mechanical and durability related properties are evaluated. Previous studies show that bricks with the appropriate values of molarity, alkali modulus, liquid-binder ratio and water glass-NaOH ratio (5–15 M, 0.15–0.9, 0.2–0.48 and 0.5–2.5 respectively) achieves a compressive strength of 5–60 N/mm 2 . Though considerable research has been carried out, application of industrial wastes in the alkali-activated bricks manufacturing are still limited and some recommendations are suggested. Geopolymeric bricks seems to be the most advantageous as they can incorporate high content of wastes. It signifies the potential use of waste materials to form alkali-activated brick as an alternate sustainable masonry option.